Leading commodity analysis of capture fisheries in Karimunjawa National Park - Ririn Irnawati; Domu Simbolon; Budi Wiryawan; Bambang Murdianto; Tri Wiji Nurani (JURNAL PERIKANAN DAN KELAUTAN, 2011)
The leading fish commodities is a kind of fish which most in demand, has high value, expected to provide a highly income compared with other types, and also giving contribution in developing capture fishery that based on efficiency concept for achieving comparative and competitive commodity in facing of trading globalization. Karimunjawa National Park (KNP) inhabited mostly by fisherman. Its area surrounds by 111.625 ha as waters. Fishing zone is dedicated for traditional fisheries. Therefore the capture fisheries in KNP should be adjusted to accommodate conservancy and utilization objectives. This research will try to answer the question about leading fish commodity which will be developed and have big contribution to economic of Karimunjawa archipelago Jepara regency Central Java province. The objective of this study is to analyze leading fish commodity in capture fishery which can increase fisherman’s prosperity in KNP. Selection of leading fish product was conducted by implementing comparative performance index. The criteria used in the research are production’s location quotient (LQ) value of fish production, LQ value of price, market demand, and fish position on food chain. The result showed that the leading fish commodity of capture fisheries in KNP are trevallies, yellow tail, and grouper. It is recommended that the government and fisherman in KNP should priority to catch fish commodity, by developing environmantal friendly fishing gears to support the sustainability of fish resources and their habitat.capture fisheries, Karimunjawa National Park, leading commodity